2010
DOI: 10.4103/0019-5154.70665
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of intelligence quotients of atopic and nonatopic children in Ibadan, Nigeria

Abstract: Background:Atopy-related illnesses such as atopic dermatitis and asthma are chronic illnesses, and children suffering from such illnesses are subjected to frequent absenteeism from school. Studies have shown that the performance of children with asthma was comparable to their healthy counterparts despite their absenteeism at school, in contrast to findings in other chronic illnesses like epilepsy.Aim:In the present study, we investigated the association between atopy and intelligence quotient (IQ) scores in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
5
7
4
Order By: Relevance
“…12 As shown in the current study, the mean overall IQ score of asthmatic patients was statistically similar to healthy children (p=0.90). Also, there was no significant difference in the verbal IQ (p=0.98) or practical IQ (p=0.98) between healthy and asthmatic children.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…12 As shown in the current study, the mean overall IQ score of asthmatic patients was statistically similar to healthy children (p=0.90). Also, there was no significant difference in the verbal IQ (p=0.98) or practical IQ (p=0.98) between healthy and asthmatic children.…”
Section: Discussionsupporting
confidence: 67%
“…The younger participants generally exhibited a lower mean IQ score than the older participants. 12 In this study however, after eliminating sex, age and the patients' level of education, the mean IQ score of patients was lower than the control group. Studies that evaluated other chronic diseases such as epilepsy have shown that these diseases affect cognitive function.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Allergies are immune responses and usually involve chronic inflammation 9 . However, whether inflammation and irritation increase the risk of neuropsychological consequences in children with atopic diseases is still unclear 10 12 . For example, allergic rhinitis is associated with significantly impaired mental health and impaired cognitive function 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It involves visuo-spatial reasoning, abstract thinking, deductive reasoning and general intelligence and covers widest range of mental ability of individuals (Raven et al, 2000). The Raven's Standard Progressive matrices has been reported as one of the best instruments for the assessment of IQ in sub-Sahara African and has also been validated for use for Nigerian children (Daramola et al, 2010;Iloh et al, 2017). Instrument: The Raven's Standard Progressive Matrices consisted of 60 problems divided into five sets (Set A, B, C, D and E), each made up of 12 problems.…”
Section: Assessment Of Intelligence Quotientmentioning
confidence: 99%